2021
DOI: 10.1002/slct.202100615
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dye Adsorption of Mixed‐Matrix Membrane by Covalent Incorporation of Metal‐Organic Framework with Poly(styrene‐alt‐maleic anhydride)

Abstract: In this study, a novel mixed-matrix membrane (MMM) based on covalent incorporation of poly(styrene-alt-maleic anhydride) (PSMA) with a metal-organic framework (MOF) UiO-66-NH 2 was prepared and utilized for dye removal from aqueous solution. The fabrication of PSMA and UiO-66-NH 2 was carried out by the amidation reaction between the maleic anhydride ring and amino functional group affording crosslinked MOF/PSMA membrane. The separate UiO-66-NH 2 and PSMA solutions were mixed before cast films were produced. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…For the N1s spectrum of BT@PE, four fitted peaks are obtained with the binding energy at 399.3, 400.4, 401.4, and 402.3 eV, respectively. The new peaks at 400.4 and 402.3 eV are assigned to N(CO) and (CO)N(CO), respectively 37–39 . The results indicate that some amino groups of BT‐NH 2 react with the MAH groups of PE‐g‐MAH to form BT@PE while others still retain in the structure of BT@PE.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…For the N1s spectrum of BT@PE, four fitted peaks are obtained with the binding energy at 399.3, 400.4, 401.4, and 402.3 eV, respectively. The new peaks at 400.4 and 402.3 eV are assigned to N(CO) and (CO)N(CO), respectively 37–39 . The results indicate that some amino groups of BT‐NH 2 react with the MAH groups of PE‐g‐MAH to form BT@PE while others still retain in the structure of BT@PE.…”
Section: Resultsmentioning
confidence: 88%
“…[34][35][36] For the N1s spectrum of BT@PE, four fitted peaks are obtained with the binding energy at 399. [37][38][39] The results indicate that some amino groups of BT-NH 2 react with the MAH groups of PE-g-MAH to form BT@PE while others still retain in the structure of BT@PE. According to the results of FTIR and XPS, the reaction process is illustrated in Figure 4, which describes the reactions from BT to BT@PE by BT-OH and BT-NH 2 .…”
Section: Structure Of Bt@pe Nanoparticlesmentioning
confidence: 91%
“…Cao and Kumar's group reported the direct covalent bonding of UiO-66-NH 2 with poly(styrene-lt-maleic anhydride) (PSMA). 133 In this study, the amide was formed by the reaction of the amino group in the MOFs with maleic anhydride in PSMA. The obtained material displayed an improved dye-adsorption performance compared with pristine PSMA.…”
Section: Synthetic Approaches For Mof–carbon-chain Polymersmentioning
confidence: 99%
“…By comparing the adsorption performance of pure PAN membranes, powder MIL101(Fe)-NH 2 , and NFM for separating dyes and acidic dye molecules in wastewater, it was shown that the NFM had better adsorption and separation performance for acidic organic ionic dyes in aqueous solution due to the synergistic effect of PAN and MIL101(Fe)-NH 2 crystals ( Figure 8 A). A mixture of poly(styrene-alt-maleic-anhydride) (PSMA) and UiO-66-NH 2 was prepared by solution casting to obtain cross-linked MOF/PSMA composite membranes with different MOF contents by Cao et al [ 109 ]. This MMM has high adsorption capacity for the separation of methylene blue (MB) and methyl orange (MO), common organic dye pollutants in wastewater.…”
Section: Applicationsmentioning
confidence: 99%